2021
DOI: 10.1186/s12866-021-02117-1
|View full text |Cite
|
Sign up to set email alerts
|

Potential of bacteriophages as disinfectants to control of Staphylococcus aureus biofilms

Abstract: Background Staphylococcus aureus is the causative agent of chronic mastitis, and can form a biofilm that is difficult to completely remove once formed. Disinfectants are effective against S. aureus, but their activity is easily affected by environmental factors and they are corrosive to equipment and chemically toxic to livestock and humans. Therefore, we investigated the potential utility of a bacteriophage as a narrow-spectrum disinfectant against biofilms formed by S. aureus. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 41 publications
(15 reference statements)
0
19
0
Order By: Relevance
“…Zhang and Hu looked at the interactions of phage and sodium hypochlorite on the formation and removal of P. aeruginosa wet biofilms and reported synergistic effects in biofilm lysis ( 49 ). Another study found that adding Triton X-100 (a nonionic detergent) could enhance biofilm removal by an S. aureus phage, although it reached the same level of removal as that of phage alone after 48 h, as determined by OD measurements ( 48 ). However, the current study reports this interaction on wet biofilms thoroughly over a range of concentrations (difference of 9 orders of magnitude in MOIs), showing that significantly lower phage concentrations can be used in combination with a chemical disinfectant to achieve the same inactivation as that with higher phage concentrations alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang and Hu looked at the interactions of phage and sodium hypochlorite on the formation and removal of P. aeruginosa wet biofilms and reported synergistic effects in biofilm lysis ( 49 ). Another study found that adding Triton X-100 (a nonionic detergent) could enhance biofilm removal by an S. aureus phage, although it reached the same level of removal as that of phage alone after 48 h, as determined by OD measurements ( 48 ). However, the current study reports this interaction on wet biofilms thoroughly over a range of concentrations (difference of 9 orders of magnitude in MOIs), showing that significantly lower phage concentrations can be used in combination with a chemical disinfectant to achieve the same inactivation as that with higher phage concentrations alone.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, less attention has been given to the interplay of phages and chemical disinfectants for use in combination treatments. Previous research has looked at simultaneous treatment with phage and disinfectants, with varying success ( 45 48 ), likely due to the confounding of the two treatments by the inactivation of the phages by the disinfectants. Also, most studies have shortcomings in the thoroughness of testing of a range of concentrations and a small dynamic quantification range since they determine removal by crystal violet staining or optical density (OD) measurement ( 46 – 49 ), which limits the amount of inactivation that can be seen.…”
Section: Introductionmentioning
confidence: 99%
“… 55 Numerous mono phages have been applied to significantly inhibit or decrease to minimum levels of viable bacteria cells in biofilms and in liquid cultures with no considerable toxicity to mammalian cells. Notable among them are biofilms formed by E. faecalis , 56 S. aureus 57 and E. coli , 58 all belonging to the ESKAPEE group. As revealed in these studies, anti-biofilm effects of lytic mono phages are concentration-dependent.…”
Section: Application Of Phages In Bacterial Biofilm Destructionmentioning
confidence: 99%
“…These preparations are active against various strains of Escherichia coli, Listeria monocytogenes, Salmonella spp., and Shigella spp. Some other preparations are being tested or under development [14][15][16]. Bacteriophages are viruses that selectively attack bacterial cells.…”
Section: Introductionmentioning
confidence: 99%